2022
DOI: 10.1038/s41598-022-12807-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress monitoring in iPSC-derived motor neurons using genetically encoded biosensors of H2O2

Abstract: Oxidative stress plays an important role in the development of neurodegenerative diseases, being either the initiator or part of a pathological cascade that leads to the neuron’s death. Genetically encoded biosensors of oxidative stress demonstrated their general functionality and overall safety in various systems. However, there is still insufficient data regarding their use in the research of disease-related phenotypes in relevant model systems, such as human cells. Here, we establish an approach for monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Specifically, Zhu and co-authors discovered that during the development of transgenic mice with rtTA expression, a stably integrated Tet-On promoter was silenced in mouse neurons, probably due to a decrease in chromatin accessibility for a tetracycline transactivator [ 79 ]. Ustyantseva and co-authors [ 80 ] showed that human motor neurons differentiated in vitro from iPSCs with a DOX-inducible expression of H 2 O 2 biosensors lost biosensor expression, but a regular supplementation of the differentiation medium with DOX helped to overcome the problem. Our data extend these observations to iPSC-derived macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, Zhu and co-authors discovered that during the development of transgenic mice with rtTA expression, a stably integrated Tet-On promoter was silenced in mouse neurons, probably due to a decrease in chromatin accessibility for a tetracycline transactivator [ 79 ]. Ustyantseva and co-authors [ 80 ] showed that human motor neurons differentiated in vitro from iPSCs with a DOX-inducible expression of H 2 O 2 biosensors lost biosensor expression, but a regular supplementation of the differentiation medium with DOX helped to overcome the problem. Our data extend these observations to iPSC-derived macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The A20 encoding nucleotide sequence was obtained by PCR from pEGFP-C1-A20 (Addgene #22141) using a Q5 ® High-Fidelity DNA Polymerase and primers ( Supplementary Table S2 ). Plasmid assembly was performed using standard molecular cloning methods by replacing the MluI-AsiGI fragment in the pCyto-roGFP2-Orp1-donor plasmid [ 80 ] with the A20 PCR product. The pAAVS1-TRE-CMV-TNFAIP3 construct assembly was confirmed by restriction analysis and Sanger sequencing (SB RAS Genomics Core Facility, Novosibirsk, Russia).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After selection, surviving colonies were mechanically transferred to 48-well plates. Transgene integration was analyzed by PCR using primers (Table 2) as previously described [35].…”
Section: Generation Of Transgenic Ipscsmentioning
confidence: 99%
“…The main advantage of iPSCs is the almost unlimited ability of cultivation and differentiation serving as a proper source of pluripotent stem cells and any type of cells in the living organism. IPSCs were successfully used for studying autoinflammatory [17,18], neurodegenerative [17][18][19][20][21][22][23][24], and other diseases. There are few attempts to create iPSCs for FMF patients, for example, a Turkish patient with a homozygous missense mutation (p.Met694Val) in the MEFV gene [25].…”
Section: Introductionmentioning
confidence: 99%